Current situation of allergy education in Mexico and other parts of Latin America - González Díaz, Sandra Nora; Martin, Bryan; De Lira Quezada, Cindy Elizabeth; Villarreal González, Rosalaura Virginia; Guzmán Avilán, Rosa Ivett; Macías Weinmann, Alejandra; Ortega Martell, José Antonio; Macouzet Sánchez, Carlos; Sánchez Borges, Mario; Rosario Filho, Nelson Augusto; Yáñez, Anahí; Guzmán Meléndez, María Antonieta; et al. (Lippincott Williams & Wilkins, 2021)
Allergic diseases are one of the most frequent chronic diseases in the world. It has been established that there is a worldwide epidemic of allergic diseases; therefore, the treatment of allergies should be acknowledged as a worldwide priority and the specialty of allergy should be considered an important field in medicine. Due to the fact that allergic diseases involve many organs, and Allergy and Clinical Immunology is one of the specialties in which physicians may be trained to treat patients of all ages, the subject in medical schools is not always taught as an individual specialty but often as part of another subject such as internal medicine or pediatrics. Certified allergists are an important contribution to health systems, providing the necessary care for patients who have allergic diseases. Undergraduate programs in many universities do not include allergy as a subject, contributing to a lack of knowledge regarding the correct management of allergic diseases. World Health Organization (WHO) recommends 1 allergist per 50,000 people; however, there is an uneven distribution of allergy and clinical immunology specialists. Most practitioners are localized mainly in larger cities and state capitals, while in other regions, specialists are still greatly needed. Support and training systems are required for allergy and clinical immunology specialists to promote continuing education and keep their clinical competence up to date, which will lead to better care for their patients. Increased exposure to the concepts of allergy and clinical immunology diagnosis and treatment in undergraduate education may also potentially lead to an increase in interest in the field of allergy and clinical immunology among physicians in training. This review will approach allergy education in Mexico and other parts of Latin America.